Adoption of conservation agriculture in Africa: impact on crop yields - Kanthal, Sahely; Mondal, Surajit; Mondal, Biswapati; Chakraborty, Debashis (International Maize and Wheat Improvement Center, 2023)
Conservation agriculture (CA) is a farming practice that is gaining popularity in Africa as a sustainable approach to increase food production. CA has numerous environmental benefits, including increased biodiversity, enhanced carbon sequestration, and improved soil quality through an increase in soil organic matter. Additionally, CA is expected to improve soil fertility, soil structure, and water retention properties over time, resulting in increased crop yields, particularly in water-scarce regions. Despite the scientific foundation and known benefits of CA, its adoption in Africa has been limited (Kassam et al., 2018). This analysis aims to identify the ideal climate, soil, crops, and duration for CA in Africa to promote its adoption more effectively.